Lipid Transfer Proteins and Membrane Contact Sites in Human Cancer - Peretti, Diego; Kim, SoHui; Tufi, Roberta; Lev, Sima (Frontiers in Cell and Developmental Biology, 2020)
Lipid-transfer proteins (LTPs) were initially discovered as cytosolic factors that facilitate lipid transport between membrane bilayers in vitro. Since then, many LTPs have been isolated from bacteria, plants, yeast and mammals, and extensively studied in cell-free systems and intact cells. A major advance in the LTP field was associated with the discovery of intracellular membrane contact sites (MCSs), small cytosolic gaps between the endoplasmic reticulum (ER) and other cellular membranes, which accelerate lipid transfer by LTPs. As LTPs modulate the distribution of lipids within cellular membranes, and many lipid species function as second messengers in key signaling pathways that control cell survival, proliferation and migration, LTPs have been implicated in cancer-associated signal transduction cascades. Increasing evidence suggests that LTPs play an important role in cancer progression and metastasis. This review describes how different LTPs as well as MCSs can contribute to cell transformation and malignant phenotype, and discusses how ‘aberrant’ MCSs are associated with tumorigenesis in human.